IoT Based Smart Classroom System - Chan, E. K. F.; Othman, M. A.; Abdul Razak, M. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Internet of Things (IoT) is no doubt will be the new revolution in the era of Industry 4.0, where every object will be connected to the server or internet for data processing and control. The attendance system that we currently use now is recorded by signing our signature on a piece of paper, which makes tracking and processing troublesome. It will need to be digitalized by using various sensors and module on it. Besides, the current conventional classroom system does not implement any energy saving system, which contributed to the high cost in paying electrical bills. Thus, in this paper, an IoT based Smart Classroom System is presented. This system consists of two features; the autonomous attendance system as well as an energy saving technology implementation. As for the autonomous attendance system, the attendance that were taken from student matric card will be digitalized and send to the server to be processed, and then the attendance records are able to be viewed via a website. Meanwhile, through the energy saving technology, students or lecturer does not purposely need to switch off the air conditioning and lights each time they leave the class anymore. Overall, the whole system will increase efficiency in terms of attendance recording and processing and save huge amount of cost spend in electricity bill.